2017
DOI: 10.1186/s12888-017-1441-9
|View full text |Cite
|
Sign up to set email alerts
|

Does one size really fit all? The effectiveness of a non-diagnosis-specific integrated mental health care program in Germany in a prospective, parallel-group controlled multi-centre trial

Abstract: BackgroundThe Network for Mental Health (NWpG-IC) is an integrated mental health care program implemented in 2009 by cooperation between health insurance companies and community mental health providers in Germany. Meanwhile about 10,000 patients have been enrolled. This is the first study evaluating the effectiveness of the program in comparison to standard mental health care in Germany.MethodsIn a parallel-group controlled trial over 18 months conducted in five regions across Germany, a total of 260 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
0
22
0
2
Order By: Relevance
“…With regard to developments in other countries, over the last decade, various pilot projects have been conducted in Germany to implement and evaluate different approaches for integrating medical-and community-based mental health care. The results of these studies are inconclusive with regard to the assessed effectiveness and efficiency of integrated mental health care approaches but also with regard to the generalisability of their outcomes [6][7][8][9][10][11]. This is mainly because, with one exception [8], none of these projects implemented evidence-based approaches to integrated mental health care, such as assertive community treatment or intensive case management.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to developments in other countries, over the last decade, various pilot projects have been conducted in Germany to implement and evaluate different approaches for integrating medical-and community-based mental health care. The results of these studies are inconclusive with regard to the assessed effectiveness and efficiency of integrated mental health care approaches but also with regard to the generalisability of their outcomes [6][7][8][9][10][11]. This is mainly because, with one exception [8], none of these projects implemented evidence-based approaches to integrated mental health care, such as assertive community treatment or intensive case management.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…In a recent study, we revealed that the additional provision of integrated mental health care components based on case management to people with mental illness, on the whole, was not more effective than CAU with regard to the primary outcome (empowerment) and most of the secondary outcomes (psychosocial impairment, met needs, and satisfaction). We suspected that this result was mainly because the services provided were insufficiently tailored to the individual needs of the service users [10].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step, the sample size for an individual randomized study is calculated. Based on studies using the 'empowerment in the process of psychiatric treatment of patients with affective and schizophrenia disorders (EPAS)' scale [26], a medium effect (0.4 SD units) of the implementation intervention on the primary endpoint is expected. This effect is detectable with an error probability of 5% (alpha) and a power of 80% by a ttest for independent samples with a sample size of 2 × 100 participants (200 in total).…”
Section: Sample Sizementioning
confidence: 99%